Pelatihan Peningkatan Pembelajaran melalui AI bagi Pelajar SMA Negeri 1 Pinrang - Andi Muhammad Arif Haris; Musrayani Usman; Mario Mario; Amirullah Amirullah; Andi Fajar; Dian Armita (Pusat Riset dan Inovasi Nasional, 2025)
The development of modern technology, especially artificial intelligence (AI), opens up great opportunities to improve the quality of education and support loval economic innovation. However, digital literacy among stundents and the use of advanced technology for the development for the development of small and medium enterprises (MSMEs) in Pinrang Regency is still low. This service activity digital literacy and creativity of Pinrang 1 State High School students through AI technology training. The training is designed to be based on small projects that combine interactive discussions, direct practice and support from expert speakers. The methods used include discussions to provide a basic understanding of AI, as well as hands-on practice sessions using AI-based tools such as Canva AI and DALL-E. The results of the training showed an improvement, reflecting their increased understanding and skills in using AI for learning and creative design. In addition, students are able to produce AI-based creative products, which are relevant to supporting learning and innovation for local MSMEs. The conclusion shows that a project-based approach, interactive discussions and direct practice are effective methods for increasing students’ technological literacy. This program has the potential to be used as a model for implementing technology in other schools, as well as supporting a local educational and economic ecosystem that is adaptive to global technological changes.